2012
DOI: 10.1007/978-1-61779-953-2_20
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Application, and Tracking of Magnetic Carbon-Coated Nanoparticles in Plants

Abstract: The behavior of nanoparticles inside plants is gaining importance for its implications in research about putative applications and toxicology. Magnetic carbon-coated nanoparticles can be easily traced through plant tissues using simple and affordable histological techniques. Here we present a methodology for the synthesis of such nanoparticles. We also describe methods for growing plants using rhizotrons (in order to observe the roots), procedures for applying the nanoparticles, taking and processing the sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Various studies have shown that nanoparticles can penetrate the cell walls in plant roots, becoming internalized in the cells and/or reaching the vascular system of the plant and being distributed to other plant organs such as the stem, leaves, and fruit (Pérez- de-Luque et al, 2012;Wang et al, 2012). Chen et al (2010) investigated the effects of carbon nanotubes on A. cepa and found that larger and more hydrophobic particles could create barriers in the pores of the cell walls, affecting the physiological state of the plant and leading to cell damage.…”
Section: Evaluation Of Phytotoxicity Of Cs/tpp Nanoparticles and Slnmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have shown that nanoparticles can penetrate the cell walls in plant roots, becoming internalized in the cells and/or reaching the vascular system of the plant and being distributed to other plant organs such as the stem, leaves, and fruit (Pérez- de-Luque et al, 2012;Wang et al, 2012). Chen et al (2010) investigated the effects of carbon nanotubes on A. cepa and found that larger and more hydrophobic particles could create barriers in the pores of the cell walls, affecting the physiological state of the plant and leading to cell damage.…”
Section: Evaluation Of Phytotoxicity Of Cs/tpp Nanoparticles and Slnmentioning
confidence: 99%
“…Studies have been conducted to obtain a better understanding of the biological effects of nanomaterials, as well as the mechanisms of their uptake and translocation in plants (Pérez- de-Luque et al, 2012). Physico-chemical characteristics of nanoparticles such as size, zeta potential, and concentration determine their interactions with plant cells and can influence the physiological responses (Thuesombat et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that nanoparticles can penetrate the cell walls in plant roots, becoming internalized in the cells and/or reaching the vascular system of the plant and being distributed to other plant organs such as the stem, leaves, and fruit (PÉREZ- DE-LUQUE et al, 2012;WANG, et al, 2012). Chen e al., (2010) investigated the effects of carbon nanotubes on A. cepa and found that larger and more hydrophobic particles could create barriers in the pores of the cell walls, affecting the physiological state of the plant and leading to cell damage.…”
Section: Evaluation Of Effects On Seedling Developmentmentioning
confidence: 99%
“…Studies have been conducted to obtain a better understanding of the biological effects of nanomaterials, as well as the mechanisms of their uptake and translocation in plants (PÉREZ-DE-LUQUE et al, 2012). Physico-chemical characteristics of nanoparticles such as size, zeta potential, and concentration determine their interactions with plant cells and can influence the physiological responses (THUESOMBAT et al, 2014).…”
Section: Introductionmentioning
confidence: 99%